Apelin and energy metabolism - Bertrand, Chantal; Valet, Philippe; Castan-Laurell, Isabelle (Frontiers in Physiology, 2015)
A wide range of adipokines identified over the past years has allowed considering white adipose tissue as a secretory organ closely integrated into overall physiological and metabolic control. Apelin, an ubiquitous peptide was known to exert different physiological effects mainly on the cardiovascular system and the regulation of fluid homeostasis until its identification as an adipokine. This has increased its broad range of action and apelin now appears clearly as a new player in energy metabolism alongside leptin and adiponectin. Apelin has been shown to act on glucose and lipid metabolism but also to modulate insulin secretion. Moreover, different studies in both animals and humans have shown that plasma apelin concentrations are usually increased during obesity and type 2 diabetes. This mini-review will focus on the various systemic apelin effects on energy metabolism by addressing its mechanisms of action. The advances concerning the role of apelin in metabolic diseases in relation with the recent reports on apelin concentrations in obese and/or diabetic subjects will also be discussed.